Development of An Integrated Moodle-Based Physical Education E-learning with Religious Content on the Topic of Pencak Silat at SMA Genrus Nusantara Boarding School Kendal (Journal of Physical Education and Sports, 2022)
Moodle is one of the e-learning platforms that can be developed to support distance learning effectively. In order not only to function as knowledge transfer, e-learning needs to be integrated with religious content. This research aims to: (1) produce an integrated Moodle-based physical education e-learning with religious content on the topic of Pencak Silat; (2) test the feasibility; and (3) test the effectiveness of e-learning product. This Research and Development uses 3 stages of 4D model (define, design, develop). The final product is produced after passing the validation by experts and two trials. Small-scale trials were conducted on 20 students and large-scale on 73 students of class X. Data analysis include feasibility test, student responses test, effectiveness test, t-test. This study shows the following results: (1) e-learning was developed using Moodle version 3.11.6 which provides several features: virtual meeting, e-books, discussion forums, learning videos, online exams; (2) e-learning has been declared feasible based on validation of expert in the field of learning media with percentage of 93,75% with “very feasible” criteria, expert in the field of physical education with percentage of 87,50% with “very feasible” criteria, and user responses with percentage of 79,50% with “good” criteria; (3) e-learning product was proven effective based on the t-test paired samples taken from the results of the pretest and posttest.